Implementation of Digital Marketing in Increasing Room Occupancy Rate at Hilton Bali Resort Hotel - Krisnha Dwi Kusuma; Ni Luh Eka Armoni; I Ketut Astawa; Putu Tika Virginiya; Indah Utami Chaerunnisah (Yayasan Sinergi Widya Nusantara, 2023)
Purpose: This study aims to analyze the application of digital marketing dimensions and the influence of digital marketing on room occupancy rates at the Hilton Bali Re-sort hotel in the Nusa Dua tourism area, Bali, Indonesia. Research methods: The data are obtained from interviews, documentation, litera-ture studies, and distributed questionnaires to 60 respondents. The question-naires data is then processed using the Structural Equation Modeling-Partial Least Square technique (SEM-PLS) by using SmartPLS that presented in the table. Findings: The implementation of each digital marketing dimension by the Hilton Bali Resort management, and the impact of digital marketing in increasing the room occupancy rate at the Hilton Bali Resort. Implication: The hotel management needs to create better quality content and promotional methods through online media so that online media customers know and are interested in products from Hilton Bali Resort.